First record of Dipolydora blakei (Annelida: Spionidae) from Europe: Greece, Mediterranean Sea - RADASHEVSKY, V. I.; SIMBOURA, N. (Mediterranean Marine Science, 2013)
The spionid polychaete Dipolydora blakei is identified from benthic samples collected in the Aegean Sea off Chalkis and the Ionian Sea off Kalamitsi, both on the coast of Greece. Adults of D. blakei are characterized by having the falcate spines of chaetiger 5 with a large lateral tooth and bristles on the convex side of a long and pointed main fang, awl-like spines in posterior notopodia, branchiae beginning from chaetiger 7 and a pygidium with two lateral lobes. This is the first report of the species from the Mediterranean Sea and European waters and the second record (after one from Brazil) outside its type locality in deep-water off New England in the north-west Atlantic Ocean. The morphology of the Greek specimens is described and illustrated and diagnostic characters of the species are discussed. The origin of these specimens in the coastal waters of Greece is uncertain and the species is considered as cryptogenic in the Mediterranean Sea. An identification key to Dipolydora species with bristle-topped falcate spines in chaetiger 5 known from the Mediterranean Sea and European waters is provided.